Rozwijanie języka edukacji szkolnej na przykładzie streszczenia - Szymańska, Marta (Z Teorii i Praktyki Dydaktycznej Języka Polskiego, 2020)
The author of the article defines school communicative situation as the one requiring from the student an ability to use specialised language known as the language of school education. According to regulations currently in force, improving the fluency in the said language is a task of teachers of all school subject because knowing it is one of the conditions of attaining educational success. The article presents a proposal to work on a summary that includes the determinants of school education language.